In situ and ex situ bioassays with Cantareus aspersus for environmental risk assessment of metal(loid) and PAH‐contaminated soils. (26th July 2021) - Louzon, Maxime; Pauget, Benjamin; Gimbert, Frédéric; Morin‐Crini, Nadia; Wong, Janine W. Y.; Zaldibar, Beñat; Natal‐da‐Luz, Tiago; Neuwirthova, Natália; Thiemann, Christina; Sarrazin, Bernard; Irazola, Mireia; Amiot, Caroline; et al.
Abstract: Environmental risk assessment of contaminated soils requires bioindicators that allow the assessment of bioavailability and toxicity of chemicals. Although many bioassays can determine the ecotoxicity of soil samples in the laboratory, few are available and standardized for on‐site application. Bioassays based on specific threshold values that assess the in situ and ex situ bioavailability and risk of metal(loid)s and polycyclic aromatic hydrocarbons (PAHs) in soils to the land snail Cantareus aspersus have never been simultaneously applied to the same soils. The aims of this study were to compare the results provided by in situ and ex situ bioassays and to determine their respective importance for environmental risk assessment. The feasibility and reproducibility of the in situ bioassay were assessed using an international ring test. This study used five plots located at a former industrial site and six laboratories participated in the ring test. The results revealed the impact of environmental parameters on the bioavailability of metal(loid)s and PAHs to snails exposed in the field to structured soils and vegetation compared to those exposed under laboratory conditions to soil collected from the same field site (excavated soils). The risk coefficients were generally higher ex situ than in situ, with some exceptions (mainly due to Cd and Mo), which might be explained by the in situ contribution of plants and humus layer as sources of exposure of snails to contaminants and by climatic parameters. The ring test showed good agreement among laboratories, which determined the same levels of risk in most of the plots. Comparison of the bioavailability to land snails and the subsequent risk estimated in situ or ex situ highlighted the complementarity between both approaches in the environmental risk assessment of contaminated soils, namely, to guide decisions on the fate and future use of the sites (e.g., excavation, embankments, and land restoration). Integr Environ Assess Manag 2022;18:539–554. © 2021 SETAC KEY POINTS: The comparison of the bioavailability to land snails and the subsequent ecotoxicological risk of the metal(loid)s and the PAHs estimated in situ or ex situ highlighted the complementarity between the field and laboratory approaches to assess the environmental risk of contaminated soils. The method is now submitted as an ISO standard (ISO 24032). This ISO standard gives tools for the assessment in situ (and ex situ) of the bioavailability and environmental risk of numerous contaminants. This original validated method should help strengthen the positioning and use of combined chemical and biological tools in environmental risk assessment of contaminated soils and sites.